Estudio de factibilidad para la creación de repostería online que ofrezca productos saludables con frutas exóticas para personas con problemas de obesidad, en Bogotá D.C. (2020)
The present feasibility study for the creation of online confectionery that offers healthy products with exotic fruits for people with obesity problems, in Bogotá DC, is divided into 6 chapters: diagnosis, market study, technical study, administrative study, legal study, and environmental and financial study. The diagnosis is an analysis of the environment that is carried out to determine situations and trends. For the project, it was analyzed based on 4 types of factors: political, economic, social, technological, environmental and legal at the Colombia and Bogotá level, with the intention of synthesizing and considering the strengths, weaknesses, threats, and opportunities that may arise in the environment. From the above factors, it will create a strategy that allows the organization to enter the country and be competitive with other companies in the bakery, pastry, and pastry sectors.